2017
DOI: 10.1038/s41598-017-13041-8
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Plasma-induced Chemical Modifications on Glutathione and Glutathione Disulphide

Abstract: Cold atmospheric pressure plasmas are gaining increased interest in the medical sector and clinical trials to treat skin diseases are underway. Plasmas are capable of producing several reactive oxygen and nitrogen species (RONS). However, there are open questions how plasma-generated RONS interact on a molecular level in a biological environment, e.g. cells or cell components. The redox pair glutathione (GSH) and glutathione disulphide (GSSG) forms the most important redox buffer in organisms responsible for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 51 publications
7
38
1
Order By: Relevance
“…While the presented spectra do not perfectly agree, most likely due to different buffers as well as pH conditions, it is apparent that disulfide bonds play a major role in determining the secondary structure of hEGF. Taking into account the strong impact of DBD treatment on disulfide bonds and its capability to oxidize disulfide bonds to, for example, cysteine sulfonic acid (R‐SO 3 H), differences in CD spectra might be due to the formation of sulfur‐containing residues all with a negative charge, thereby further promoting unfolding of the structure, as shown for longer treatment times. The additional introduction of C═O bounds, as indicated by FTIR spectroscopy, might also assist in the unfolding process.…”
Section: Resultsmentioning
confidence: 99%
“…While the presented spectra do not perfectly agree, most likely due to different buffers as well as pH conditions, it is apparent that disulfide bonds play a major role in determining the secondary structure of hEGF. Taking into account the strong impact of DBD treatment on disulfide bonds and its capability to oxidize disulfide bonds to, for example, cysteine sulfonic acid (R‐SO 3 H), differences in CD spectra might be due to the formation of sulfur‐containing residues all with a negative charge, thereby further promoting unfolding of the structure, as shown for longer treatment times. The additional introduction of C═O bounds, as indicated by FTIR spectroscopy, might also assist in the unfolding process.…”
Section: Resultsmentioning
confidence: 99%
“…46,47 Thiol groups are one of the major targets for plasma-generated species. [48][49][50] Hence, CAP impact can yield to (non-enzymatic) post-translational modications (PTMs), with some of which transport signicant inuence in cellular signaling. [51][52][53][54] However, so far no specic member of the various ROS or RNS could be attributed to be the major driver of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[26] The appearance of these peaks indicates the formation of aS b ÀS complex (II), as shown in Reaction (3). [27] In this case, it suggested that an acylamide bond is formed in molecular structure (III) (Reaction (4);F igure 1b). [27] The peak was diminished as the annealing temperature (AT) was increased, indicating the breaking of the CÀSb ond.…”
Section: Resultsmentioning
confidence: 95%
“…[25] Moreover,R amans cattering at 300 cm À1 was ascribed to C 3v symmetric modes of the SbS 3 pyramid structure. [27] The peak was diminished as the annealing temperature (AT) was increased, indicating the breaking of the CÀSb ond. The resonant peak located at 660 cm À1 is assigned to the CÀSs tretching vibration.…”
Section: Resultsmentioning
confidence: 99%